PENGEMBANGAN SISTEM INFORMASI BERBASIS WEB UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN ARSIP KEPEGAWAIAN DI BPJS KETENAGAKERJAAN CABANG MAROS - Pertiwi Solo, Jessika Olivia; Putra, Anhar Dana (ADMIT: Jurnal Administrasi Terapan, 2025)
BPJS Ketenagakerjaan Maros Branch is an institution operating in the field of employment insurance, aiming to provide protection for workers throughout their careers and into retirement. The institution offers five main programs designed to safeguard workers' well-being during active employment and ensure security during post-employment periods. Preliminary observations revealed a key issue in the human resources archiving process, which is still conducted manually. This conventional system presents several inefficiencies, particularly in terms of time consumption for data retrieval, storage management, and data updating. In response to these challenges, this study aims to design and develop an information system to enhance the efficiency and effectiveness of the personnel archive management process. The development methodology employed is the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. This research focuses on the development of a web-based information system intended to facilitate and streamline the management of personnel records. The system incorporates key features such as structured employee data storage, archive retrieval based on various criteria, user access management, and automated report generation. Testing results indicate that the developed system significantly accelerates the document retrieval process, reduces the risk of data loss, and simplifies the updating of personnel records.